Doppler echocardiographic criteria in patency assessment of composite grafts from left internal thoracic artery - Leitão,Maria Claudia A. (2013)
OBJECTIVES: The purpose of our study was to establish, with an entirely noninvasive method, transthoracic Doppler echocardiography, criteria for patency of composite left internal thoracic artery grafts when placed on the left anterior descending artery and other branches of the left coronary system. METHODS: The control group comprised 20 patients with single graft and 20 patients with composite graft; all forty having their patency confirmed by coronary angiogram (CA). In this control group, two Doppler echocardiographic variables, diastolic mean velocity-time and integral diastolic peak velocity to systolic peak velocity ratio were recorded. For each variable, established cut-off points were established, using the ROC (Receiver Operator Characteristic) curves, to identify criteria which could differentiate the composite grafts. Only patients with composite grafts were included in the 159-patients study group. The criteria established by the cut-off points in the control group were then applied to detect patency using a diastolic fraction of > 0.5 as the gold standard. The sensitivity, specificity, and positive and negative predictive values of these two criteria were determined. RESULTS: In the control group, cut-off points of 0.71 and 0.09m were established for the diastolic peak velocity/systolic peak velocity ratio and for diastolic mean velocity-time integral, respectively. In the study group phase, the sensitivity and negative predictive value of the diastolic peak velocity/systolic peak velocity > 0.71 criterion were 36% and 11%, respectively. Diastolic mean velocity-time integral > 0.09m criterion, were 40% and 10.48%. The specificities and positive predictive values of each criterion were 100%. CONCLUSION: Values reaching the criteria established for each variable indicate high probability of composite graft patency. Lower values have a large proportion of false negatives and are not conclusive as patency criteria.